DEVELOPMENT THE CHARACTER VALUES OF ELEMENTARY SCHOOL STUDENTS THROUGHT SATURDAY AND SUNDAY CAMP ACTIVITIES : A CASE STUDY AT SDN TOBAT IV BALARAJA - Darmawan, Darmawan; Robiasnyah, Firman; Halimah, Nur (Didaktika, 2021)
Scouting education is a practical educational process, which is carried out in the open with interesting, challenging, fun, and directed activities. one form of activity is Saturday and Sunday camp, where SDN Tobat IV Balaraja makes this activity a flagship activity in the annual work program. The purpose of this research is to describe how the process of implementing Saturday-Sunday camp activities, analyzing the values contained in the activities, and the implications of these activities in fostering student character. This research uses a qualitative approach with a case study method. The research subjects in this study were fourth and fifth-grade students, scout coaches, and principals of SDN Tobat IV Balaraja. Data collection techniques in this study were semi-structured interviews, documentation studies, and closed questionnaires. For data analysis, namely data reduction, data presentation, and conclusion drawing/verification. This research resulted in the process of Saturday-Sunday camp activities starting from the arrival of students, the opening ceremony, following the activities that have been arranged and ending with the closing ceremony. The results of the analysis on these activities contained 13 characters values. The implications of Saturday and Sunday camp activities resulted in a questionnaire of 90% of students answering correctly and 10% of students answering incorrectly. So that it can be concluded, this Saturday and Sunday camp can be a recommendation for activities that shape the character of students